Diskresi Dalam Pengangkatan Pejabat Kepala Daerah Dari Unsur TNI-Polri - Ardiansyah, Raihan; waluyo, Waluyo; Candrakirana, Rosita (Jurnal Ilmu Hukum Reusam, 2024)
This research aims to find out and review the laws and regulations regarding the appointment of Acting Regional Heads from the TNI / Polri elements. This research is a descriptive juridical-empirical legal research with a research approach using a statutory approach, case approach, conceptual approach and elaborates with a qualitative approach. The research data sources come from primary data and secondary data. Primary data is the result of interviews and secondary data is primary legal material and secondary legal material. The analysis technique used in this research uses the deduction method. The results of this study indicate that the appointment of Acting (Pj) regional heads who come from active TNI / Polri elements is a maladministration event because it is contrary to statutory regulations because it does not fulfil the arrangements for filling high leadership positions in accordance with statutory regulations. And in fact, the appointment of Acting Regional Heads from TNI / Polri elements is a form of discretion and does not reflect the concept of public service delivery.